Information technology in primary school management - Sunaengsih, C; Djuanda, D; Isrokatun, I; Syahid, A A; Nuraeni, A (Journal of physics. Conference series, 2019)
Difficult acceptance of scientific and technological advancement is a common fact. Therefore, it is important to recognize school's capability to build conducive environment for the implementation of new technology as soon as possible. Such recognition will facilitate information technology implementation in school management. This study employs descriptive research method using quantitative approach to uncover the actual description of information technology acceptance factors in the management of primary schools in Indonesia. Total subjects of this study is 173 primary school teachers, consisted of 38 male teachers and 135 female teachers. The findings show that the school community will accept information technology more willingly if the technology in question is up to date.